Association of childhood adiposity measures with adulthood knee cartilage defects and bone marrow lesions: a 25-year cohort study. Issue 8 (August 2018) - Meng, T.; Thayer, S.; Venn, A.; Wu, F.; Cicuttini, F.; March, L.; Dwyer, T.; Halliday, A.; Cross, M.; Laslett, L.L.; Jones, G.; Ding, C.; et al.
Summary: Objective: To describe the associations between childhood adiposity measures and adulthood knee cartilage defects and bone marrow lesions (BMLs) measured 25 years later. Methods: 327 participants from the Australian Schools Health and Fitness Survey (ASHFS) of 1985 (aged 7–15 years) were followed up 25 years later (aged 31–41 years). Childhood measures (weight, height and skinfolds) were collected in 1985. Body mass index (BMI), overweight status and fat mass were calculated. Participants underwent 1.5 T knee magnetic resonance imaging (MRI) during 2008–2010, and cartilage defects and BMLs were scored from knee MRI scans. Log binomial regressions were used to examine the associations. Results: Among 327 participants (47.1% females), 21 (6.4%) were overweight in childhood. Childhood adiposity measures were associated with the increased risk of adulthood patellar cartilage defects (Weight relative risk (RR) 1.05/kg, 95% confidence interval (CI) 1.01–1.09; BMI 1.10/kg/m 2, 1.01–1.19; Overweight 2.22/yes, 1.21–4.08; fat mass 1.11/kg, 1.01–1.22), but not tibiofemoral cartilage defects. Childhood adiposity measures were not significantly associated with adulthood knee BMLs except for the association between childhood overweight status and adulthood patellar BMLs (RR 2.87/yes, 95% CI 1.10–7.53). These significant associations persisted after adjustment for corresponding adulthood adiposity measure. Conclusion: Childhood adiposity measures were associated with the increased risk of adulthood patellar cartilage defects and, to a lesser extent, BMLs, independent of adulthood adiposity measures. These results suggest that adiposity in childhood has long-term effects on patellar structural abnormalities in young adults.